SOURCES OF LAW OF THE UZBEK STATE IN THE MIDDLE AGES (World Bulletin of Management and Law, 2023)
The legal sources of Uzbek statehood in the Middle Ages were multifaceted and complex, reflecting the colorful and dynamic nature of the socio-political landscape of the region. The convergence of nomadic traditions, Islamic legal guidelines, and imperial administrative systems created a multifaceted legal framework that provided for the governance and social structure of Uzbek territories. This article is aimed at an in-depth study of these legal sources and their role in the formation of the legal identity of Uzbek statehood in the Middle Ages.